2014
DOI: 10.1177/1043454214553707
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Psychosocial Associates of Nonadherence in Adolescents With Cancer

Abstract: The current study examined adherence to medication regimens among adolescents with cancer by applying the Pediatric Self-Management Model. Adolescents and their parents reported on adherence to medication, reasons for nonadherence, and patient-, family-, and community-level psychosocial variables. Adolescent- and parent-reported adherence were significantly correlated, with about half of the sample reporting perfect adherence. The majority reported “just forgot” as the most common reason for missed medication.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…Anticipatory guidance including a discussion of common barriers to adherence, previous experiences taking medication, and strategies to improve medication adherence should be provided immediately prior to the transfer of self‐management responsibilities to the patient and/or family and whenever there is a change in the medication regimen . Children and adolescents with cancer and their families describe multiple barriers to medication adherence that can be addressed with behavioral intervention including forgetting, being away from home when doses are due, difficulty in swallowing pills, taste of medications, and not feeling well . Observational studies suggest that interventions targeting family support and patient psychosocial functioning (i.e., depressive symptoms) may improve adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anticipatory guidance including a discussion of common barriers to adherence, previous experiences taking medication, and strategies to improve medication adherence should be provided immediately prior to the transfer of self‐management responsibilities to the patient and/or family and whenever there is a change in the medication regimen . Children and adolescents with cancer and their families describe multiple barriers to medication adherence that can be addressed with behavioral intervention including forgetting, being away from home when doses are due, difficulty in swallowing pills, taste of medications, and not feeling well . Observational studies suggest that interventions targeting family support and patient psychosocial functioning (i.e., depressive symptoms) may improve adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents with cancer and their families describe multiple barriers to medication adherence that can be addressed with behavioral intervention including forgetting, being away from home when doses are due, difficulty in swallowing pills, taste of medications, and not feeling well . Observational studies suggest that interventions targeting family support and patient psychosocial functioning (i.e., depressive symptoms) may improve adherence. As behavioral and multicomponent interventions providing such guidance are more effective in improving medication adherence than educational interventions alone and have been shown to improve self‐efficacy, cancer‐related knowledge, and adherence, clinicians are encouraged to consider partnering with relevant disciplines (i.e., psychology, social work, and child life) to develop procedures for assessing barriers and delivering behavioral interventions as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms listed on the cards included those supported by previous studies of adherence among AYAs (i.e., Hullmann et al, 2014) and adherence decision-making (i.e., Sung et al, 2003) (see Table 3). In addition, AYAs were provided with a stack of blank cards and asked to create a card for any mechanism that impacted adherence decision-making not listed on a previous card (e.g., “my husband’s support”).…”
Section: Methodsmentioning
confidence: 99%
“…The few studies examining this question have identified broad constructs including deficits in information (i.e., lack of medication knowledge), limited family social support, and psychosocial difficulties (i.e., depressive symptoms) that predict non-adherence among AYAs with cancer (Hullmann, Brumley, & Schwartz, 2014; Kennard et al, 2004; Tebbi et al, 1986). While these studies identify predictors of adherence behavior, the use of broad measures and single point assessments of adherence prevent conclusions as to the mechanisms that account for these relationships (Quittner, Modi, Lemanek, Ievers-Landis, & Rapoff, 2008).…”
mentioning
confidence: 99%
“…Treatment intensity is relevant given that it might be related to other important variables of interest, including school attendance, family functioning, patient or family member distress [3] and survivor health-related quality of life [4, 5]. Additionally, it is often important to establish that treatment intensity is not related to certain variables, such as fatigue [6], physical activity [7] or adherence to medical regimens [8]. While treatment intensity may be related to the level of risk for late effects, they are not necessarily directly related.…”
Section: Introductionmentioning
confidence: 99%